Renal scintigraphy in children with urinary tract infections - Ajdinović Boris; Krstić Zoran; Dopuđa Marija; Jauković Ljiljana (Vojnosanitetski Pregled)
Background/Aim. To determine the incidence of abnormal Technetium Tc 99m Dimercaptosuccinic Acid (Tc99m DMSA) renal scintigraphy findings in the children with urinary tract infection (UTI), and to evaluate the difference between the children with UTI and vesico-ureteral reflux (VUR), and the children with UTI without VUR. Methods. Tc99m DMSA renal scintigraphy was performed in 170 children with UTI, mean age 7.07 years (1 month to 14 years, 137 were girls and 33 were boys). In 88 of the children, VUR was proved by micturating cystouretherography (MCU), while in 82 VUR could not be detected by MCU. VUR was graded in accordance with MCU recommended by the international study of VUR. In 13 of the children the grade of VUR was grade I, in 30 was grade II, in 23 grade III, in 17 grade IV, while the grade V was in 5 of the children. Findings of Tc99m DMSA renal scintigraphy were classified as: 1 - normal, 2 - probably normal, 3 - equivocal, 4 - probably abnormal, and 5 - abnormal. The degree of the significance of the difference of the findings was estimated using χ2, taking p < 0.01 as the limit of statistical significance. Results. Of the total number of 170 studied children, the abnormal findings were detected in 30% (51/170), normal findings in 62% (106/170), and equivocal in 8% (13/170). In the children with UTI and VUR, the incidence of abnormal findings was 49% (43/88), of normal 43% (38/88), and of equivocal findings 8% (7/88). All the children with VUR grade V had the abnormal findings (the incidence of the abnormal findings was 100%). In the children with VUR grade IV, the abnormal findings were 71%. In the children with VUR grade I, 77% of the findings were normal, in the children with VUR grade II, 53% of the findings were normal and in the children with VUR grade III, 30% of the findings of renal scintigraphy were normal. In the children with UTI without VUR, the incidence of abnormal findings was 10% (8/82), of normal findings 83% (68/82), and of equivocal findings 7% (6/82). The incidence of abnormal findings was significantly higher in the children with UTI and VUR than in those with UTI without VUR (p < 0.01). Also, the incidence of the abnormal findings was higher in the children with VUR grades IV and V than in the children with VUR grade I (p < 0.01). Conclusion. DMSA renal scintigraphy in the children with ITU revealed the abnormal findings in 30% of the cases. The incidence of the abnormal findings was significantly higher when VUR was present, as well as if the grade of VUR was higher. Our results confirmed that Tc99m DMSA renal scintigraphy was a very important technique in the evaluation of the children with ITU.